2020
DOI: 10.1007/s00340-020-07478-5
|View full text |Cite
|
Sign up to set email alerts
|

Cryogenic platform for coupling color centers in diamond membranes to a fiber-based microcavity

Abstract: We operate a fiber-based cavity with an inserted diamond membrane containing ensembles of silicon vacancy centers (SiV −) at cryogenic temperatures ≥ 4 K. The setup, sample fabrication and spectroscopic characterization are described, together with a demonstration of the cavity influence by the Purcell effect. This paves the way towards solid-state qubits coupled to optical interfaces as long-lived quantum memories.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 66 publications
2
13
0
Order By: Relevance
“…So far, open microcavities have been coupled to a multitude of quantum systems including atoms [224], ions [82,225], molecules [80,226], quantum dots [227], rare earth ions [228], optomechanical systems [229], and color centers in both nanodiamonds [108][109][110][111][112]126] and diamond membranes [128,[230][231][232].…”
Section: Open Fabry-perot Microcavitiesmentioning
confidence: 99%
“…So far, open microcavities have been coupled to a multitude of quantum systems including atoms [224], ions [82,225], molecules [80,226], quantum dots [227], rare earth ions [228], optomechanical systems [229], and color centers in both nanodiamonds [108][109][110][111][112]126] and diamond membranes [128,[230][231][232].…”
Section: Open Fabry-perot Microcavitiesmentioning
confidence: 99%
“…A long coherence time for these defect related electronic states is facilitated by the wide-bandgap material (≈5.5 eV for bulk diamond), since diamond crystals are relatively free of background nuclear spins and feature a low electron concentration as well as low phonon scattering rate [21,22]. These color centers, such as the nitrogen-vacancy (NV) center [23,24], the silicon-vacancy (SiV) center [25,26] or the germanium-vacancy center (GeV) [27,28], exhibit a high photostability at room temperature, polarizability and allow a practicable control of coherent single spins, hence serving as single-photon emitters. In particular, the prominent NV color center presents a promising candidate for quantum memory bits due to its long-lived and well-defined spin quantum states [29].…”
Section: Introductionmentioning
confidence: 99%
“…However, nanofabrication produces near-surface damage, and in particular for the NV center, it was found that this leads to a substantial degradation of the optical coherence properties. The most promising approach is to use minimally processed diamond membranes with a thickness of a few micrometers where color centers remain far away from surfaces, which are introduced into open-access microcavities by bonding to one of the cavity mirrors [25,26,36]. Such microcavities allow for spatial and spectral tunability in order to controllably match the geometrical and spectral overlap of a cavity mode with a selected color center.…”
Section: Introductionmentioning
confidence: 99%
“…We consider that the remaining thickness variation can be further improved by optimization of the polishing process and technique [48]. We note that color centers such as NV and SiV centers can be created in the SCDM via CVD growth [41] or ion implantation [49].…”
mentioning
confidence: 99%
“…The removal of the ion-damaged layer and thinning of the SCDM down to the desired thickness are made possible by oxygen-plasma RIE during the SCDM fabrication. We note that color centers such as NV and SiV centers can be created in the SCDM via CVD growth [39] or ion implantation [45].…”
mentioning
confidence: 99%